STIGMA SOSIAL PADA KELUARGA PASIEN CORONAVIRUS DISEASE 2019 DI KECAMATAN SUNGAILIAT KABUPATEN BANGKA - Firginia Elviera; Putra Pratama Saputra; Amir Dedoe (Jurnal Ilmiah Dinamika Sosial, 2021)
This research is about the stigma that appears in Sungailiat District, Bangka Regency which is aimed at the families of Coronavirus Disease 2019 patients who are not necessarily infected but still get negative stigma from the community. This study aims to describe the form of social stigma and the way families of Coronavirus Disease 2019 patients manage the stigma given by the community of Sungailiat District. The research method used is a qualitative descriptive research type. The data was collected from observation, interviews, and literature study. Researchers found that society stigmatizes families of Coronavirus Disease 2019 patients by limiting social contact in the form of isolating, alienating, and avoiding caused by fear, vigilance, and lack of confidentiality in society. The families of Coronavirus Disease 2019 managing stigma namely following the wishes of the community to keep their distance from them and continuing to interact with the surrounding community to make it look normal. Keywords: Coronavirus Disease 2019, Patients Family, Social Stigma